Intracranial Subarachnoid Haemorrhage Caused by Cervical Spinal Dural Arteriovenous Fistulas: Case Report - Zhao, Junjie; Esemen, Yagmur; Rane, Neil; Nair, Ramesh (Frontiers in Neurology, 2021)
Cervical spinal vascular abnormalities commonly presented with progressive myelopathy as a result of venous congestion. They are not very prone to bleed and tend to be underdiagnosed due to their subtle clinical presentation. We came across a rare case of intracranial subarachnoid hemorrhage caused by cervical spinal dural fistula in the Imperial College Healthcare NHS Trust Hospitals/UK in June 2020. We diagnosed her under strict evidence base medicine guidance which otherwise would have been missed. We discussed her case in several multidisciplinary team (MDT) meeting and she was treated under the joint care of neurology and neurosurgical team. She made full recovery and discharged home with no neurological defects or complications. Here we reported this case with all the evidence we gathered from our MDT discussion. We hoped our experience would help improve the diagnosis and management protocol for future patients with similar condition.